2010
DOI: 10.1111/j.1600-0404.2009.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin labeling demonstrates that focal amygdalar glutamatergic agonist infusion leads to rapid diffuse cerebral activation

Abstract: Objectives-To investigate acute effects of intra-amygdalar excitatory amino acid administration on blood flow, relaxation time and apparent diffusion coefficient in rat brain.Materials and Methods-Several days after MR-compatible cannula placement in right basolateral amygdala, anesthetized rats were imaged at 7T. Relative CBF was measured before and 60 minutes after infusion of 10 nanomoles KA, cAMPA, ATPA, or normal saline using arterial spin labeling. Quantitative T 2 and diffusion weighted images were acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Reconstruction of the aiMRI maps. All the simulations were performed on homewritten programs 49 in MATLAB 2018a (MathWorks, Natick, MA, USA). In the phantom experiments where the signal in some voxels reached noise floor at large TEs, the signal correction for Rician noise was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Reconstruction of the aiMRI maps. All the simulations were performed on homewritten programs 49 in MATLAB 2018a (MathWorks, Natick, MA, USA). In the phantom experiments where the signal in some voxels reached noise floor at large TEs, the signal correction for Rician noise was performed.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we found that intra-amygdalar injection of 10 nm KA, AMPA or ATPA GluR agonists evoked bilateral seizure activity and increased rCBF (6). In this study, we sought to determine whether isolated seizures, whether single or repetitive, induced by threshold doses of excitatory amino acids (EAAs), and not leading to status epilepticus, would lead to structural and pathological changes in rats.…”
mentioning
confidence: 95%